Peningkatan Pemahaman Masyarakat Terhadap Covid-19 di BTN Griya Nugratama Cianjur Jawa Barat - Fransiska Puspita Dewi; Syamsul Hadi (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2020)
Kuliah Kerja Nyata (KKN) UNS Tanggap Covid-19 in BTN Griya Nugratama, Cianjur, West Java is a community service activity by Sebelas Maret University students to accelerate the handling of the Covid-19 pandemic that is hitting various countries, including Indonesia. Implementation of KKN UNS Tanggap Covid-19 is expected to develop practical skills of students in helping to resolve the issues or problems that occurred in the community during pandemic. The main programs of KKN UNS Tanggap Covid-19 at BTN Griya Nugratama RT05/RW14 are online socialization about Covid-19 with informative and educational infographics and poster through social media, making and distributing hand sanitizers with recommended use by WHO; the secondary programs are video making of jamu (traditional drink), and participating in Covid-19 online volunteer. The implementation of the KKN UNS Tanggap Covid-19 went smoothly and all KKN program activities at BTN Griya Nugratama RT05 / RW14 have been carried out as expected. The community also actively participates and appreciates KKN activities as well.